Religious Festivals in Turkey and India to Promote Cultural Heritage - Alaknanda Munshi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
Celebrating religious festivals is a public expression of beliefs that strengthens the believer's relationship with God. This study aims to examine Religious Festivals in Turkey and India to Promote Cultural Heritage. This research employs a qualitative research method, namely by reviewing scientific articles, books and research journals. The result of this study revealed that Festivals are an essential form of cultural tourism in which cultural activities are leveraged to generate more visitors. Religious festivals can strengthen their cultural heritage and become more focused as a cultural destination by engaging in promotional activities. While the success of a festival is in part determined by the organizer, if a festival is not effectively organized, the destination will lose not only revenue but also its image.